A Smooth Trajectory Planning for a Semi Autonomous Wheelchair Using Particle Swarm Optimization - Ngo, Van Thuyen (Old Journal, 2017)
This paper presented a motion planning algorithm for a semi autonomous wheelchair for severely disable people. The D* was used to determine an optimal path to its goal position. An optimal motion planning using particle swarm optimization (PSO) to navigate the wheelchair to its global goal. The D* search guarantees a global path from the start position to the goal if there is any while the particle swarm optimization search provides a smooth movement for the wheelchair from one step to another. The simulation in Player/Stage showed that the wheelchair could find an optimal path and the planned trajectory was smoother compared with the motion planner using potential field only.